The study of family businesses from a global perspective - possibilities and limitations - Pérez, Paloma Fernández (História Econômica & História de Empresas, 2012)
The privatization wave of the 1980s and 1990s meant a reduction in taxes to the wealthiest dynasties in developed and developing countries. It also meant a global process of mergers and acquisitions which benefitted public and private corporations, many family owned businesses. At a national scale family controlled firms have historically been a fundamental source of stability in regional and local creation of wealth and employment. Due to this historical perception of family businesses by societies, politics, and governments, family controlled firms have been supported and benefitted by legislation throughout the world. As economic historians, however, we should try to keep some distance with the object of our study, and critically analyze about appropriate definitions of what family businesses are and how they compare internationally. Also, we must clarify our assumptions about the relationships between family businesses, politics, and society throughout time, and see path dependence and complexity where management literature sees convergence and homogeneity. A comparison of the largest family controlled businesses in Brazil, Mexico and China suggests the utility of business history to provide nuanced and critical views about the significance of family firms in the world.